PELAKSANAAN LELANG TANAH WARISAN OLEH KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (CONTOH KASUS PENETAPAN PENGADILAN AGAMA JAKARTA PUSAT NOMOR 003/PDT.EKS/2018/PAJP JO PENETAPAN PENGADILAN AGAMA JAKARTA PUSAT NOMOR 003/PDT.EKS/2017/PAJP JO PUTUSAN PENGADI - Degio Verell Seppkio; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2022)
Auction is a way to make a sale by gathering several auction enthusiasts for the object being auctioned, then selling it by means of the interested person bidding in writing or verbally. Minister of Finance Regulation No. 27/PMK.06/2016 becomes the basis for conducting auctions in Indonesia. The implementation of the auction in the Decision of the Religious Court Number 003/Pdt.Eks/2018/PAJP in conjunction with the Decision of the Religious Court Number 003/Pdt.Eks/2017/PAJP in conjunction with the Decision of the Religious Court Number 015/Pdt.G/2014/PAJP becomes a question of how the house is possible which is still occupied can be auctioned without being known while the house is still occupied. In addition, the auction used is an execution auction, namely an auction that is carried out based on an existing decision and should be confiscated against the object that is the basis for the execution auction, and is controlled by the Religious Court in this case, but the object of the auction is still occupied by the heirs. In this study the author will further analyze the existing problems using normative research methods by examining secondary legal materials, documentation studies, and the analytical method used deductively by examining the existing problems by first looking for the major premise and the minor premise.